Physical and biological features of an active rock glacier in the Italian Alps. (November 2014) - Gobbi, Mauro; Ballarin, Francesco; Compostella, Chiara; Lencioni, Valeria; Seppi, Roberto; Tampucci, Duccio; Caccianiga, Marco
We report on the key physical features of an active rock glacier that influence the distribution of plants and arthropods. We also perform a comparison with neighboring scree slope and alpine grassland to test whether the environmental features of the rock glacier drive the presence of specific species assemblages. Compared with scree slope and grassland, the studied rock glacier provides particular physical features that determine the presence of unique species. Plant distribution is mainly driven by grain size. Arthropod distribution is linked to grain size, with cold-adapted species found on areas with coarse-grained deep debris, which also shows a distinctive temperature regime with very low values throughout the year. On the basis of these findings, we advance the hypothesis that rock glaciers provide specific ecological conditions creating potential refugia for cold-demanding species during warm climatic periods.